PENGARUH PERCEIVED USEFULNESS, PERCEIVED EASE OF USE DAN PERCEIVED RISK TERHADAP CONTINUE INTENTION TO USE MELALUI KEPUASAN PENGGUNA APLIKASI MOBILE BANKING BCA - Nur Faizatun Nufus Mashfiatul Kamalia; Amma Fazizah (Universitas Diponegoro, 2025)
The purpose of this study is to find out how much influence Perceived Usefulness (X1), Perceived Ease Of Use (X2) and Perceived Risk (X3) on Continue Intention To Use (Y2) through Satisfaction (Y1) of BCA Mobile Banking users. This study uses a survey approach with a quantitative method. This data collection is through the distribution of questionnaires or questionnaires to 100 respondents. This data analysis technique uses Path Analysis and is assisted by using SPSS version 20. The sampling method of this study uses purposive sampling with certain criteria. The results of this study showed: 1). perceived usefulness (X1) to satisfaction (Y1). 2). perceived ease of use (X2) had no significant effect on satisfaction (Y1). 3). perceived risk (X3) has a significant effect on satisfaction (Y1). 4). perceived usefulness (X1) has no significant effect on continue intention to use (Y2). 5). perceived ease of use (X2) has a significant effect on continue intention to use (Y2). 6). perceived risk (X3) does not have a significant effect on continue intention to use (Y2). 7). Satisfaction (Y1) has a significant effect on continue intention to use (Y2).